The formulation of guidelines for an occupational health and safety program to address women’s health concerns of mineworkers at a selected coalmine in Mpumalanga South Africa - Mogale, Ramadimetja S. (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.